2014
DOI: 10.3389/fnhum.2014.00163
|View full text |Cite
|
Sign up to set email alerts
|

Action relevance in linguistic context drives word-induced motor activity

Abstract: Many neurocognitive studies on the role of motor structures in action-language processing have implicitly adopted a “dictionary-like” framework within which lexical meaning is constructed on the basis of an invariant set of semantic features. The debate has thus been centered on the question of whether motor activation is an integral part of the lexical semantics (embodied theories) or the result of a post-lexical construction of a situation model (disembodied theories). However, research in psycholinguistics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
62
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(75 citation statements)
references
References 71 publications
(134 reference statements)
11
62
0
2
Order By: Relevance
“…In line with our previous findings (Aravena et al, 2012;Aravena et al, 2014;Frak et al, 2010), the present results confirm that the processing of action words within a sentential context focused on body action provokes a sustained increase in grip force levels starting within the first 300-ms period after word onset-that is, within the time frames associated in the model proposed by Friederici (2002) with the retrieval of word form and word category. Note that the rather early onset of these effects is in line with studies in which event-related potentials have been analyzed during spoken sentence processing.…”
Section: Artifact Rejectionsupporting
confidence: 92%
See 2 more Smart Citations
“…In line with our previous findings (Aravena et al, 2012;Aravena et al, 2014;Frak et al, 2010), the present results confirm that the processing of action words within a sentential context focused on body action provokes a sustained increase in grip force levels starting within the first 300-ms period after word onset-that is, within the time frames associated in the model proposed by Friederici (2002) with the retrieval of word form and word category. Note that the rather early onset of these effects is in line with studies in which event-related potentials have been analyzed during spoken sentence processing.…”
Section: Artifact Rejectionsupporting
confidence: 92%
“…Justifications for these criteria are given in the BResults and discussion^section. Following Aravena et al (2014;Aravena et al, 2012), to evaluate the time course of language-induced motor activation, we drew on an influential neurophysiological model of spoken sentence comprehension by Friederici (2002). According to this model, information about syntactic structure is formed in a first phase on the basis of information about word category approximately 100-300 ms after word onset.…”
Section: Experiments 2 Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies, among many others (e.g., Sato et al, 2008;Mirabella et al, 2012;Aravena et al, 2012Aravena et al, , 2014, suggest that verb-induced motor activation is not a rigid, inflexible affair, but is instead sensitive to attentional and situational factors that we are only beginning to understand. It is essential to realize, however, that the mere fact that there is some variability regarding when and how the motor features of verb meanings are retrieved does not imply that those features are not really long-term components of the concepts or that they are not really subserved by the precentral motor cortices.…”
Section: Processing Dynamicsmentioning
confidence: 94%
“…Finally, as an illustration of nonlinguistic context effects, in an fMRI study Papeo et al (2012) found that not only action verbs but also purely stative verbs significantly recruited the motor cortex in certain circumstances-specifically, when they were encountered after subjects first performed a mental rotation task using a motor-oriented rather than a visuospatially oriented strategy. Taken together, these studies, among many others (e.g., Mirabella et al 2012;Aravena et al 2012Aravena et al , 2014Schuil et al 2013), suggest that verb-induced motor activation is by no means a rigid, inflexible affair, but is instead quite sensitive to attentional and situational factors (for a broader perspective, see Lebois et al in press).…”
Section: Speed and Automaticity Of Processingmentioning
confidence: 70%